Making an Inclusive Community Through Inclusive, Barrier-Free Theatre - Bailey, Sally; Burr, Britt; Dickinson, Paige; Marie, Tracena; Woolsey, Patti; Yadon, Michelle (My University, 2019)
Drama therapists can work under many business structures when establishing a therapeutic theatre company to serve their clients and their communities. The business models the authors have found to provide homes for their acting companies are applicable to any type of therapeutic theatre. These include working under the auspices of already-established arts, educational, and service nonprofits to creating their own LLC or 501(c)3 nonprofit. This article offers action steps and advice so more drama therapists can establish their own theatre companies.
Keywords: Therapeutic Theatre; Barrier-Free Theatre; Drama Therapy; Devised Theatre; Inclusive Theatre; Performance